Enterprises Break The Circle Of Bullying : Psychoeducation Bullying Prevention Student Public Health - Asbanu, Aprilia Natasya Aurola; Malihing, Rossaliani; Lengga, Felichia Findyanti; Banik, Merlinda Hartati; Riberu, Rosalia Kartona; Manafe, Yuni Maharani; Benu, Juliana Marlin Yusrianty (Fakultas Psikologi Universitas Pancasila, 2025)
.